2021
DOI: 10.1055/s-0041-1730042
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Flap Protection during Third Molar Surgery: A Literature Review

Abstract: The purpose of this review was to analyze how the retraction and protection of lingual flap (LF+) could influence the incidence of lingual nerve injury (LNI) during third molar extraction, as compared with protocols that do not involve handling of lingual tissue (LF). A literature review was performed from the “Medline” and “Scopus” medical databases, using the keywords “lingual nerve” and “third molar surgery.” From the selected articles, the mean values for transitory and permanent LNI’s incidence were elabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A recent review [41] examines how retracting and safeguarding the lingual ap could impact the occurrence of lingual nerve injury (LNI) during third molar extraction, in contrast to protocols not involving manipulation of lingual tissue. In the studies reviewed, the incidence of temporary LNI ranged between 0 and 8.94%, while permanent LNI ranged between 0 and 1.60%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review [41] examines how retracting and safeguarding the lingual ap could impact the occurrence of lingual nerve injury (LNI) during third molar extraction, in contrast to protocols not involving manipulation of lingual tissue. In the studies reviewed, the incidence of temporary LNI ranged between 0 and 8.94%, while permanent LNI ranged between 0 and 1.60%.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the IAN and LN during and after MTM surgery can have a variety of causes, including direct trauma to the nerve from rotating instruments during ostectomy or separation, sharp transection during flap preparation, or more indirect damage from compression or chemical disturbance from a hematoma or injection of local anesthetics [ 28 , 29 , 30 , 31 ]. Apart from complete transection of a nerve, which is usually noticed immediately during surgery, it is often difficult to determine the exact cause of nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…14 On the other hand in a study by Ramadorai and colleagues employed the buccal flaponly technique and found just one case (0.078%) of lingual nerve injury in an audit of 1276 cases of mandibular surgical extractions. 15 In the current study surgical technique employing both buccal and lingual flaps was used for the surgical access of mandibular third molars. The lingual mucoperiosteal flap reflected cleanly and retracted with the blunt end of the molt periosteal elevator which was passively placed to protect the lingual flap.…”
Section: Intact Nervementioning
confidence: 99%